A comparative study between primary resection anastomosis versus Hartmann’s procedure with colostomy in patients of colonic mass presenting with acute intestinal obstruction - A., Kishore Kumar; Jadhav, Kirankumar P.; Jeughale, Kishor B.; Chavan, Manisha T.; Deshmukh, Aniket B.; Pinjari, Riyaz (International Journal of Research in Medical Sciences, 2025)
Background: Acute intestinal obstruction is a life-threatening condition, with colonic masses being a significant cause. The choice of surgical procedure primary resection and anastomosis (PRA) or the Hartmann procedure (HP) with colostomy-depends on multiple factors, including patient stability and the extent of obstruction. Both techniques have distinct advantages and associated risks, with ongoing debate about their comparative outcomes in emergency settings. Methods: A prospective observational study was conducted over 18 months at the Department of Surgery, B. J. M. C. and S. G. H. Pune. Sixty patients with colonic masses presenting with acute intestinal obstruction were analysed. Patients were divided into two groups: those undergoing PRA and those undergoing HP. Data on perioperative parameters, postoperative complications, and outcomes were collected and statistically analysed using statistical package for the social sciences (SPSS) version 18.0. Results: Among the 60 patients, PRA was associated with shorter hospital stays (mean 7.57 days) compared to HP (mean 12.33 days; p=0.000). Postoperative wound infections occurred in 25% of patients, with higher rates in the HP group (33.3%) than the PRA group (16.7%). Colostomy-related complications were exclusive to the HP group (23.3%). There was no significant difference in mortality between the two groups (6.7% each), but PRA patients experienced a higher rate of anastomotic leaks (6.7%). Conclusions: PRA offers faster recovery and fewer long-term complications in select patients, while HP remains safer for those with severe contamination or hemodynamic instability. Individualized patient assessment is crucial for determining the optimal surgical approach.